2014
DOI: 10.1080/15374416.2014.913250
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Behavior Mediates the Intergenerational Association of Parent and Child Offspring ADHD Symptoms

Abstract: Although there are likely to be multiple mechanisms underlying parent attention-deficit/hyperactivity disorder (ADHD) symptoms as a key risk factor for offspring ADHD, potential explanatory factors have yet to be reliably identified. Given that parent ADHD symptoms independently predict parenting behavior and child ADHD symptoms, we tested whether individual differences in multiple dimensions of positive and negative parenting behavior (i.e., corporal punishment, inconsistent discipline, positive parenting beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
32
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 83 publications
4
32
0
1
Order By: Relevance
“…Our findings converge with studies (Chronis-Tuscano et al, 2011; Tung et al, 2014) suggesting that harsh parenting mediates the relation between parental ADHD and child ADHD and ODD symptoms. Moreover, the present study indicates that these processes emerge in the early development of ADHD.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings converge with studies (Chronis-Tuscano et al, 2011; Tung et al, 2014) suggesting that harsh parenting mediates the relation between parental ADHD and child ADHD and ODD symptoms. Moreover, the present study indicates that these processes emerge in the early development of ADHD.…”
Section: Discussionsupporting
confidence: 89%
“…However, only a handful of studies have directly tested whether parenting mediates the relation between parental ADHD and child ADHD and ODD symptoms. In a prospective study, Tung et al (2014) found that corporal punishment mediated the relation between parent and child ADHD. Chronis-Tuscano et al (2011) found that negative parenting mediated the relation between maternal ADHD symptoms and reductions in child disruptive behavior symptoms following parent training for children with ADHD.…”
Section: Parenting Practices As a Mediator Of The Relation Between Pamentioning
confidence: 99%
See 1 more Smart Citation
“…high neuroticism and surgency, Martel et al, 2014], parental [i.e. parenting behavior and parent depression, Tung et al, 2014] and environmental [i.e. media use, Nikkelen et al, 2014 and family income, Larsson et al, 2014] factors mediate the link between genetic variation and ADHD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, recent work has also indicated that parenting dimensions, specifically the use of corporal punishment strategies, mediated associations between parental and offspring ADHD (Tung et al 2015), suggesting that parenting dimensions may play a key role in understanding the transmission of ADHD. Along these lines, significant G×E effects involving inconsistent parental discipline have also been observed for ADHD (Martel et al 2011), indicating that the impact of negative (or positive) parenting on youth functioning may be dependent upon inherited vulnerability factors.…”
mentioning
confidence: 99%